Psychometric Evaluation of BRT-13B: A Shorter Version of the Benchmark Resilience Tool - Sharma, Shikha; Sharma, Sanjeev K. (Prabandhan: Indian Journal of Management, 2015)
The Indian IT Industry is operating in an era of risk and instability. Success and survival in this uncertain environment demands the organizations to be resilient, which is not about responding to one time crisis. It is about continuously anticipating and adjusting to change. Research reveals that an organization having resilient people, systems, and processes can adjust to meeting the varying needs of its market with more confidence, making it essential to have an organization centric measure of resilience. Despite the growing importance of the concept, there are only few reliable and valid instruments available in the literature, and most importantly, none of the available instruments have been used to measure the resilience capacity of IT organizations. Keeping this gap in mind, this study evaluated the factor structure and psychometric properties of the recently developed, a shorter version of Benchmark Resilience Tool (BRT-13B) by considering a sample of Indian IT executives. An empirical research was conducted by considering 160 employees of 12 information technology firms located in few select states of Northern India and registered with NASSCOM. The data were collected using 13 items, BRT-13B scale. Confirmatory factor analysis verified the original two-factor structure. In this study, 75.537 % of the variance was jointly explained by the two factors (Planning and Adaptive Capacity). The results supported the dimensionality, reliability (Î±=0.888) and validity of the BRT-13 B instrument for measuring the IT executives' resilience.